Introducing the family of "Sen" transformers a set of power flow controlling transformers. - Sen, K.K.
Real and reactive power flow in an AC transmission line are independently controlled by connecting, to a transmission line, a series-compensating voltage, which is variable in magnitude and at variable angle with respect to the transmission line voltage as well as the prevailing line current. The traditional technology of transformer and tap changer is used to implement this novel technique. An additional voltage regulation capability can also be implemented. The speed of tap changer operation determines the response time of this power flow controller, which is quite adequate in most utility applications. The response time can be improved if suitable solid-state switches are available to replace the mechanical taps.
Keywords: AC transmission line; FACTS; Sen transformers; UPFC; Load flow control; Mechanical taps; Phase shifters; Power electronics; Power flow controlling transformers; Power transmission; Power transmission control; Prevailing line current; Reactive power flow; Real power flow; Series-compensating voltage; Solid-state switches; Tap changer; Tap changer operation speed; Transmission line voltage; Unified power flow controller; Variable angle; Voltage regulation capability